The role of the private sector in preparing for humanitarian operations - A multiple-case study including DP-DHL, MasterCard and Cisco - Hult,Amanda; Persson Segell,Lovisa (2017)
There are many actors included in the humanitarian system, such as NGOs, UN humanitarian agencies and governments. However, a gap in the humanitarian system can be identified where the traditional actors lack resources, which provides an opportunity for the private sector to be more involved, particularly in preparing for humanitarian operations. Therefore, in this research, a multiple-case study has been performed with three private businesses; DP-DHL, MasterCard and Cisco, with the purpose to understand the present role of the private sector in preparing for humanitarian operations and the possibility to improve this role. Both benefits and some challenges have been revealed related to the involvement of the private sector. An understanding of their role has been obtained where it has been found that there are many possibilities for the private sector to engage in preparing for humanitarian operations. The outcomes of the engagements studied in this research imply that successful initiatives are achievable and factors of success have been formulated. These can indicate what areas should be invested in to achieve successful initiatives in the future.
Keywords: Disaster; risk; DRR; preparedness; private sector; humanitarian system; humanitarian operations; case study; partnership